Wasted cabbage (Brassica oleracea) silages treated with different levels of ground corn and silage inoculant - Rezende, Adauton Vilela de; Silveira Rabelo, Carlos Henrique; Machado da Silva, Max Rossi; Haerter, Carla Joice [UNESP]; Veiga, Rosane Micaela (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2015)
Our objective was to evaluate the chemical composition, fermentation profile, and aerobic stability of cabbage silages treated with ground corn and inoculant. The evaluated treatments were: addition of 200, 300, 400, 500, and 600 g of ground corn per kilogram of cabbage (fresh matter basis), with or without a bacterial inoculant composed of Lactobacillus plantarum and Pediococcus pentosaceus. As expected, ground corn additions increased the dry matter (DM) content of cabbage silage, and high values were observed for the highest level of addition (540 g kg(-1)). Conversely, the crude protein, neutral detergent fiber, acid detergent fiber, and lignin contents decreased with ground corn additions. The in vitro dry matter digestibility coefficients increased slightly with ground corn additions, but all cabbage silages had digestibility higher than 740 g kg(-1) of DM. In the fermentation process, the pH values of cabbage silages increased linearly because of the high levels of ground corn addition. Cabbage ensiled with 200 and 300 g kg(-1) of ground corn had high ammonia N production and fermentative losses (effluent and gas). Cabbage silage treated with 600 g kg(-1) of ground corn had lower maximum pH values during aerobic exposure, but all silages had constant temperature during aerobic exposure. The ensiling of wasted cabbage is possible and we recommend the application of 400 g kg(-1) ground corn to improve the silage quality, whereas the use of the inoculant is unnecessary.
Keywords: additives; by-product; lactic acid bacteria; nutritive value